2022
DOI: 10.1016/j.heliyon.2022.e08876
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adoption of improved bread wheat technologies in Ethiopia: empirical evidence from Meket district

Abstract: This study was conducted in Meket district of Amhara National Regional State in northern Ethiopia. Crosssectional data was used for the study, which was collected from 214 randomly selected agricultural households using a structured interview protocol. With the help of the double hurdle model, factors were identified that influence the probability of adoption and the intensity of use of improved bread wheat varieties and associated technologies in the study area. The first hurdle of the model suggests that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The marginal effect of this model demonstrates that a household's likelihood of adopting better wheat varieties increases by 4.0% for every additional extension contact that is made. The results are in line with Negussie et al (2022); Susie & Bosena (2020) findings that an increase in the frequency of extension visits could increase the probability of adoption by 4.96 %.…”
Section: Association Between Adoption and Socioeconomic Characteristicssupporting
confidence: 90%
“…The marginal effect of this model demonstrates that a household's likelihood of adopting better wheat varieties increases by 4.0% for every additional extension contact that is made. The results are in line with Negussie et al (2022); Susie & Bosena (2020) findings that an increase in the frequency of extension visits could increase the probability of adoption by 4.96 %.…”
Section: Association Between Adoption and Socioeconomic Characteristicssupporting
confidence: 90%
“…Therefore, access to extension services increases adoption. In addition, Siyum et al (2022) also found out that the frequency of extension visits significantly and positively affects the probability of adoption of improved bread wheat production technology, increasing the probability by 4.96% upon an increment of extension contact. Also, Chandio and Jiang (2018) on their research concluded that 1% increase in extension contact increases the probability of adoption of improved varieties of wheat by 0.02%.…”
Section: Identification Of Factors Affecting the Adoption Of Improved...mentioning
confidence: 90%
“…Ullah et al [29] reported that input availability had a positive and signi cant in uence on farmers' adoption decisions. According to the ndings in [30][31][32]. Farmer education had a positive and signi cant in uence on adoption.…”
Section: Introductionmentioning
confidence: 98%